VALORIZATIONOFTHEROLEOFTHEEARTHWORMS IN THE BIO REMEDIATION OF CONTAMINATED SOIL - MERAH Azhar (My University, 2025)
Soil contamination by synthetic pesticides poses a major threat to ecosystems and human health, particularly in areas of intense agricultural activity. Bioremediation has emerged as a sustainable solution to mitigate this pollution. This study evaluates the role of the earthworm Aporrectodeatrapezoidesinthedegradationandstabilizationofinsecticideinsoil,in the presence of the bioindicator plant Viciafaba. Laboratorytests were carried out using four treatments, with two pollutant doses, in the presence or absence of earthworms. The results show that the introduction of worms promotes the restoration of soil quality, increases biological activity and improves Viciafaba growth despite the presence of the contaminant.TheseobservationssuggestthatAporrectodeatrapezoidesplays akeyroleinthe bioremediation of contaminated soils, through biological transformation and detoxification mechanisms. ------------------------------------------------------------------------------------------------------------------------------ يشكلتلوثالتربةبالمبيداتالاصطناعيةتهديدًاكبيرًاللأنظمةالبيئيةوصحةالإنسان،خاصةفيالمناطقالتيتشهدنشاطًا زراعيًامكثفًا.وقدظهرتالمعالجةالحيويةكحلمستدامللتخفيفمنهذاالتلوث.تهدفهذهالدراسةإلىتقييمدوردودة الأرض"أبوركتودياترابييزويدس"فيتحللوتثبيتالمبيد-فيالتربة،بوجودنبات"الفولالعريض" كمؤشر حيوي. أُجريتتجاربمخبريةوفقًالأربعةمعالجات،بجرعتينمنالملوث،فيوجودوغيابديدانالأرض. أظهرتالنتائجأنإدخالديدانالأرضيعززاستعادةجودةالتربة،ويزيدالنشاطالبيولوجي،كمايُحسنمننمونباتالفولالعريضعلىالرغممنوجود الملوث.وتشيرهذهالملاحظاتإلىأندودة الأرضتلعبدورًا رئيسيًافيالمعالجةالحيوية للتربةالملوثة،منخلالآلياتحيويةللتحولوإزالةالسمية. ----------------------------------------------------------------------------------------------------------------------------------------------- La contamination des sols par les pesticides synthétiques constitue une menace importante pour les écosystèmes et la santé humaine, en particulier dans les régions où l'activité agricole est intense. La bioremédiation est apparue comme une solution durable pour atténuer cette pollution. Cette étude évalue le rôle du ver de terre Aporrectodeatrapezoidesdans la dégradation et la stabilisation d’insecticide dans le sol, en présence d’une plante bioindicatriceVicia faba. Des essais en laboratoire ont été réalisés selon quatre traitements, avecdeuxdosesdupolluant,enprésenceetenabsencedesversdeterre. Les résultats montrent que l’introduction des vers favorise la restauration de la qualité du sol, augmente l’activité biologique et améliore la croissance de Vicia fabamalgré la présence du contaminant. Ces observations suggèrent que Aporrectodeatrapezoidesjoue un rôle clé dans la bioremédiation des sols contaminés, à travers des mécanismes biologiques de transformation et de détoxification.
Keywords: Bioremediation; Earthworms; Aporrectodea trapezoides; Soil contamination; Viciafaba. المعالجةالبيولوجية؛ديدانالأرض؛أبورِكتودياترابيزويدس؛تلوثالتربة؛الفولالعريض Bioremédiation; Vers de terre; Contamination des sols; Vicia faba.